Prevalence of obesity and overweight among primary school children in a district of Istanbul, Turkey - SAVE, DİLŞAD (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: We aimed to investigate the prevalence of obesity and overweight and their relationship with environmental factors among children aged 5-10 years at a primary school in an Istanbul district. Materials and Methods: The data of this cross-sectional study were collected from a random selection of 177 students and their families. Students' heights and weights were measured in a standardized way for calculating their body mass index. The World Health Organization growth reference was used for the definition of obesity and overweight status. Results: The prevalence of obesity and overweight was 12.4% and 20.9%, respectively, with no difference between girls and boys. A significant increase in the percentage of obesity and overweight was observed with increasing age (p = 0.001). Having an obese or overweight father (p = 0.001) and a working mother (p=0.003) were associated with an increase in childhood obesity. Conclusion: The findings of this study imply that obesity or overweight among primary school children is associated with increasing age, having an obese or overweight father and having a working mother. State organizations, schools, physicians and other healthcare professionals must work together to encourage children and their families to adopt healthy lifestyles and to improve their awareness of obesity.
Keywords: Childhood obesity; Public health; Prevalence; BODY-MASS INDEX; PHYSICAL-ACTIVITY; ASSOCIATIONS; ADOLESCENTS; CHILDHOOD; NUTRITION; HEALTH